Adsorption Properties of O2 onCr5 Nanostructures: A DFT Study - Mohammad T. Baei; Ali Kazemi Babaheydari; Parviz Torabi (E-Journal of Chemistry)
Based on the density functional theory (DFT) adsorption properties of oxygen molecule on Cr5 nanostructures at various positions (top, bridge and central sites) were investigated. Geometry optimizations and vibrational frequencies of them were carried out at B3LYP level of theory with LANL2DZ and 6-31G* basis sets using Gaussian 98 suites of program. Their thermodynamic properties were estimated. We have also investigated the total electronic properties, HOMO, LUMO and energy gap for Cr5 nanostructures with O2. The result showed that the adsorption of O2 on Cr5 nanocluster in horizontal bridge site is the most stable state of adsorption and its binding energy is strong, -145.88 kcal/mol.